2022
DOI: 10.3390/genes13081432
|View full text |Cite
|
Sign up to set email alerts
|

Eye and Hair Color Prediction of Ancient and Second World War Skeletal Remains Using a Forensic PCR-MPS Approach

Abstract: To test the usefulness of the forensic PCR-MPS approach to eye and hair color prediction for aged skeletons, a customized version of the PCR-MPS HIrisPlex panel was used on two sets of samples. The first set contained 11 skeletons dated from the 3rd to the 18th centuries AD, and for each of them at least four bone types were analyzed (for a total of 47 samples). In the second set, 24 skeletons from the Second World War were analyzed, and only petrous bones from the skulls were tested. Good-quality libraries we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…The origin of the allelic drop-in events in the analysis of SNP markers via PCR-MPS has been questioned by numerous researchers [ 10 , 12 , 25 , 27 , 42 , 43 ]. The error rate generated by the Ion Torrent technology is quite high (≥ 1%), but they consisted mainly in insertion/deletion artefacts [ 44 ] (whilst the Illumina technology is mainly subjected to misinsertions [ 45 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the allelic drop-in events in the analysis of SNP markers via PCR-MPS has been questioned by numerous researchers [ 10 , 12 , 25 , 27 , 42 , 43 ]. The error rate generated by the Ion Torrent technology is quite high (≥ 1%), but they consisted mainly in insertion/deletion artefacts [ 44 ] (whilst the Illumina technology is mainly subjected to misinsertions [ 45 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In 2008, three studies highlighted the role of HERC2 and described the SNP located in intron 86, rs12913832:A/G, as a major eye color predictor strongly associated with OCA2 expression levels [ 13 , 24 , 25 , 41 ]. More recently, it was experimentally demonstrated that this SNP acts as an enhancer, regulating OCA2 transcription by distantly modulating chromatin folding [ 27 ].…”
Section: The Genetic Basis Of Eye Color: Oca2 and ...mentioning
confidence: 99%
“…Significant progress has been made with the implementation of next generation sequencing (NGS) technology to provide precious information about identity, biogeographic ancestry, paternity, and the possibility of adding massive parallel sequencing (MPS) with many DNA predictors, useful for forensic purposes such as FDP [ 8 , 9 , 10 ]. There are currently available a variety of genotyping assays based on MPS technologies developed to predict EVCs from DNA recovered in a crime scene, i.e., to reconstruct the appearance traits from highly decomposed remains, the biogeographic ancestry, the estimation of the age of the subject, and the age of bone remains, which certainly allow a more comprehensive approach toward the FDP applications [ 11 , 12 , 13 ]. The development of the MPS multiplex assay and the introduction of single-cell sequencing consent to enhance the EVC prediction, especially when low amounts of DNA or mixed traces were collected [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic phenotyping using next-generation sequencing (NGS) technology seems to be another interesting aspect of DNA isolation [86]. So far, DNA isolated from human remains from World War II allowed for determination of the eye and hair color in 100% of the studied cases [87]. Furthermore, cartilage tissue was used in phenotyping, attempting to reconstruct the deceased's face using alar cartilage dimensions, among other things [88].…”
Section: Forensic Genetic Analysismentioning
confidence: 99%